Вплив інсулінотерапії на стан серцево-судинної системи у дітей, хворих на цукровий діабет - Леженко, Г. О.; Руднєва, І. В.; Пашкова, О. Є. (Clinical Endocrinology and Endocrine Surgery, 2011)
Results of heart rate variability and Doppler cardiometry of 91 diabetic children are generalized. It was established that for diabetic patients the formation of myocardium electric instability by way of prolongation of interval QT and left ventricular remodeling in the form of concentric remodeling, concentric and eccentric hypertrophy are inherent. It was shown that human insulin glargin and glulisin has optimal influence on the cardiovascular system of children with diabetes.